2004
DOI: 10.1111/j.0022-0477.2004.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative dominance hypothesis explains interaction dynamics in mixed speciesAlnus rubra/Pseudotsuga menziesiistands

Abstract: 1 We used repeated measurements of tree growth and population-level and neighbourhood conditions from three mixed Alnus rubra/Pseudotsuga menziesii forests in the Pacific Northwest, USA to investigate why previous results regarding the importance of neighbourhood competition as a determinant of plant growth were inconsistent. 2 We propose that relative dominance of a particular species determines the importance of neighbourhood interactions, and tested whether growth performance of both species at various stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…A positive relationship often exists between the size of an individual relative to the population and growth rate (Schmitt et al 1987;D'Amato and Puettmann 2004), a pattern also found in this study. Individual tree growth is strongly limited by the number of larger trees near the subject tree (D' Amato and Puettmann 2004;Puettmann et al 2009b).…”
Section: Tree Growthsupporting
confidence: 87%
“…A positive relationship often exists between the size of an individual relative to the population and growth rate (Schmitt et al 1987;D'Amato and Puettmann 2004), a pattern also found in this study. Individual tree growth is strongly limited by the number of larger trees near the subject tree (D' Amato and Puettmann 2004;Puettmann et al 2009b).…”
Section: Tree Growthsupporting
confidence: 87%
“…The next superior competition selection approach, CZR 0.4h , was simple in practice and in accordance with studies showing that, the optimal influence zone radius strongly depended on the tree's initial dimensions (D'Amato & Puettmann, 2004;Sims et al, 2009). Considering the third suitable competitor selection method, similar to several other studies, the opening angle of 50°-60° performed well (Biging & Dobbertin, 1995;Pretzsch, 2009;Oheimb et al, 2011) where bigger angles (80° and 100° in this study) mainly de-11 Analysis of Competition Between Individual Trees young stands, where the stands are usually dense, because these types of indices give more weight to trees that are closer to the subject tree.…”
Section: Discussionsupporting
confidence: 69%
“…Evidence is mounting that tree interactions are a spatially explicit process (e.g., Wagner and Radosevich 1998;D'Amato and Puettmann 2004;Roberts and Harrington 2008). In contrast to even-aged, even-spaced stands, the spatial variability in growing conditions within stands with high spatial variability renders stand-level indices less suitable for predicting growth of individual trees (Bigging and Dobbertin 1995).…”
Section: Discussionmentioning
confidence: 99%